PELATIHAN PELATIHAN & SOSIALISASI PENGGUNAAN PORTAL KAJIAN ILMU KEISLAMAN PADA MAJLIS TAKLIM DKM NURUL HUDA - Buhori Muslim (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Community service is an obligation that exists in the Tri Dharma Perguruan Tinggi (PT), based on this, the service, conducts Research and Service in South Cianjur, Research and Service is precisely carried out at DKM Nurul Huda, this service is a continuation of Research on the creation of a recitation portal in the mosque managed by DKM Nurul Huda, DKM Nurul Huda has problems in informing the study activities it manages which often do not reach the community because the distance between RT/RW is far apart while the community already has the tools to receive this information in the form of smartphone, so that the servants feel that making a portal is an alternative to convey information on Islamic studies, another obstacle is Nurul Huda's understanding of DKM towards SITI, so it is necessary to hold training and socialization on the use and management of this portal. The method used is to listen, pay attention and practice until the DKM administrators who manage the recitation are able to operate this portal. and at the end of this service, a good understanding of the management of the portal was produced, the DKM management was able to convey information, even studies on the portal so that pilgrims who did not come could know the study and know the material presented by Ustad.